2021
DOI: 10.12890/2021_003094
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and Respiratory Failure: Mind the Shunt!

Abstract: When stroke patients present with respiratory failure, the first thought that clinicians have is that it is probably related to aspiration pneumonia. However, other causes should be considered, such as intracardiac or intrapulmonary shunts, that could present with paradoxical embolism. Paradoxical embolism is a rare entity defined by the occurrence of a venous thrombotic event associated with a systemic arterial embolism. Frequently, paradoxical embolism presents with platypnoea-orthodeoxia syndrome. Platypnoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…PDE may also occur in association with atrial septal defects (ASDs), ventricular septal defects (VSDs), or pulmonary arteriovenous malformations (PAVMs) [7]. In contrast to PFO, patients with VSD causing Eisenmenger syndrome or PAVM have persistent right-to-left shunts that can result in PDE [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…PDE may also occur in association with atrial septal defects (ASDs), ventricular septal defects (VSDs), or pulmonary arteriovenous malformations (PAVMs) [7]. In contrast to PFO, patients with VSD causing Eisenmenger syndrome or PAVM have persistent right-to-left shunts that can result in PDE [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary infections, while not signi cantly affecting acute phase mortality, elevate the risk of death and lead to longer hospital stays during the recovery phase, potentially exposing patients to more pathogens [22,23] . Moreover, these infections can lead to severe complications like sepsis and respiratory failure [21,24,25] . highlighting the critical need for early detection and management of high-risk ICH patients.…”
Section: Effect Of Pulmonary Infection On Convalescent Patients With ...mentioning
confidence: 99%
“…Another study showed that as one of the important factors, pulmonary infection leads to prolonged hospitalization of ICH patients, which makes patients more likely to be exposed to pathogens during hospitalization, thus aggravating pulmonary infection or causing other infections [23]. Pulmonary infection may also lead to sepsis, respiratory failure and epilepsy in convalescent patients with intracerebral hemorrhage [21,24,25]. Therefore, pulmonary infection has a huge impact on the prognosis of convalescent patients with intracerebral hemorrhage, and it is necessary for clinical staff to identify ICH patients at high risk of pulmonary infection as early as possible.…”
Section: Effect Of Pulmonary Infection On Convalescent Patients With ...mentioning
confidence: 99%